2022
DOI: 10.3390/plants11151968
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dittrichia viscosa Aquaporin Nip1.1 Gene as Marker for Arsenic-Tolerant Plant Selection

Abstract: Dittrichia viscosa (L.) Greuter is gaining attention for its high genetic plasticity and ability to adapt to adverse environmental conditions, including heavy metal and metalloid pollution. Uptake and translocation of cadmium, copper, iron, nickel, lead, and zinc to the shoots have been characterized, but its performance with arsenic is less known and sometimes contradictory. Tolerance to As is not related to a reduced uptake, but the null mutation of the aquaporin Nip1.1 gene in Arabidopsis makes the plant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The rapid population spread of D. graveolens in new areas is aided by its annual lifecycle, self-compatibility, high fecundity, wind dispersal, and high germination rate ( Rameau et al 2008 ; Brownsey et al 2013a ; Lustenhouwer et al 2018 ). The species thrives in human-disturbed habitat such as roadsides and industrial sites which is facilitated by tolerance to environmental stressors such as high salinity ( Grašič et al 2016 ; Šajna et al 2017 ), heavy metals ( Shallari et al 1998 ), and possibly to arsenic as found in D. viscosa ( De Paolis et al 2022 ). It has a high secondary metabolite diversity and toxicology with 262 compounds discovered to date ( Ponticelli et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid population spread of D. graveolens in new areas is aided by its annual lifecycle, self-compatibility, high fecundity, wind dispersal, and high germination rate ( Rameau et al 2008 ; Brownsey et al 2013a ; Lustenhouwer et al 2018 ). The species thrives in human-disturbed habitat such as roadsides and industrial sites which is facilitated by tolerance to environmental stressors such as high salinity ( Grašič et al 2016 ; Šajna et al 2017 ), heavy metals ( Shallari et al 1998 ), and possibly to arsenic as found in D. viscosa ( De Paolis et al 2022 ). It has a high secondary metabolite diversity and toxicology with 262 compounds discovered to date ( Ponticelli et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA isolation and cDNA synthesis were performed as reported by De Paolis et al [ 47 ]. Total RNA was isolated from basal rosette leaves of 6 week-old chicory plants (Selvatica, Zuccherina di Trieste, Brindisina, Esportazione, Rossa Italiana, Galatina) subjected, or not, to drought stress for a further 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, D. viscosa (L.) Greuter was found to possess a DvNip1 gene homolog. The expression of DvNip1.1 in D. viscosa clonal lines cultivated under different stressful conditions was also observed, and the proportion of DvNip1.1 translation levels found in both shoots and roots is suggested as a plausible selective marker for recognizing highly resistant D. viscosa plants [101]. Previously Anglana et al [102] investigated D. viscosa's ability to absorb, translocate, and proliferate in different levels of Cd 2+ , As 3+, and As 5+ .…”
Section: Recent Biotechnological Approaches For Potential Phytoremedi...mentioning
confidence: 96%